2015
DOI: 10.4049/jimmunol.1402719
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Heat Shock Protein 70 Homolog Ssa1 Contributes to Pulmonary Expansion of Cryptococcus neoformans during the Afferent Phase of the Immune Response by Promoting Macrophage M2 Polarization

Abstract: Numerous virulence factors expressed by C. neoformans (C. neo) modulate host defenses by promoting non-protective Th2-biased adaptive immune responses. Prior studies demonstrate that the HSP70 homologue, Ssa1, significantly contributes to serotype-D C. neo virulence through the induction of laccase, a Th2-skewing and CNS-tropic factor. In the current study, we sought to determine whether Ssa1 modulates host defenses in mice infected with a highly virulent serotype A (serA) strain of C. neo (H99). To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 61 publications
2
44
0
Order By: Relevance
“…These results indicate that SHO1 expression is not required for the immediate adaptation of C. neoformans to lung environment but it supports optimal growth rate of the pathogen at time points consistent with the innate fungal control (Eastman et al, 2015) and the development of the polarized adaptive immunity (Osterholzer et al, 2009; Eastman et al, 2015), suggesting that SHO1 may have a role in promoting immunomodulatory effects of C. neoformans .…”
Section: Resultsmentioning
confidence: 86%
“…These results indicate that SHO1 expression is not required for the immediate adaptation of C. neoformans to lung environment but it supports optimal growth rate of the pathogen at time points consistent with the innate fungal control (Eastman et al, 2015) and the development of the polarized adaptive immunity (Osterholzer et al, 2009; Eastman et al, 2015), suggesting that SHO1 may have a role in promoting immunomodulatory effects of C. neoformans .…”
Section: Resultsmentioning
confidence: 86%
“…Mice infected with a Cryptococcus neoformans strain lacking Ssa1 -Hsp70 ortholog -presented decreased lung fungal burden compared to controls [24]. It was also proposed that Ssa1 directly promoted the polarization of macrophages to an M2 phenotype in order to evade host protective immune responses [24]. Ssa1-lacking Candida albicans strain showed a reduced virulence in murine model of candidiasis due to a reduced capacity to be endocytosed by endothelial and oral epithelial cells [25].…”
Section: Discussionmentioning
confidence: 97%
“…Mice infected with a Cryptococcus neoformans strain lacking Ssa1 -Hsp70 ortholog -presented decreased lung fungal burden compared to controls [24]. It was also proposed that Ssa1 directly promoted the polarization of macrophages to an M2 phenotype in order to evade host protective immune responses [24].…”
Section: Discussionmentioning
confidence: 98%
“…Eastman et al (2015) determined the effect of Ssa1 in mice infected with a highly virulent serotype A (serA) strain of C. neoformans (H99—Ssa1 deleted) and, surprisingly, noted that, unlike serotype D, H99-serA does not require Ssa1 for laccase expression. The authors further showed that Ssa1 directly promotes early M2 macrophage polarization to improve fungal growth during the innate phase of the immune response.…”
Section: Controlmentioning
confidence: 99%